Exploring the use of a cartoon as a learner scaffold in the planning of scientific investigations - Ramnarain, Umesh (Faculty of Education, University of the Free State, 2012)
Despite curriculum imperatives, in South Africa and worldwide, for learners to have more autonomy in investigations, they remain largely teacher controlled with learners having only limited opportunities in planning. This design-based study explored how a cartoon can be employed in a Grade 9 Natural Sciences class in prompting learners to plan investigations. This innovation followed a continuous cycle of design, enactment, analysis and redesign, synonymous with design-based research. Data were collected through classroom observations of the cartoon being used in practice by a Grade 9 teacher, and interviews with her. The effectiveness of this innovation was established by assessing learner plans using an adapted rubric. The findings indicate that a cartoon having an extended dialogue between characters on a science concept, accompanied by a prompt sheet, is an effective support mechanism in planning investigations. Using this support mechanism, learners were able to write a plan which included stating the problem, formulating the hypothesis, identifying variables, apparatus and a step-by-step procedure for conducting the investigation as well as describing how the collected data would be analysed to address the stated hypothesis. The findings also reveal that such a support mechanism, apart from shifting learners towards more autonomy, does invite learners to engage in the scientific discourse, wh ich often serves as a barrier to science learning.
Keywords: Scientific investigations; Cartoons; Practical work; Autonomy; Planning; Prompt sheet; Learners